Reduced glutathione ameliorates sepsis-induced acute kidney injury in mouse model: involvement of cuproptosis - Lu Wang; Long Jiang; Jingjing Wang; Wen Tang; Zhigao Wang; Rennan Guo; Daquan Zhang (Renal Failure)
Background Cuproptosis, a copper-induced form of programmed cell death, has been implicated in the pathogenesis of acute kidney injury (AKI) and sepsis. Reduced glutathione (GSH), a potent antioxidant, exhibits both anti-inflammatory and anti-oxidative properties. However, its potential role in modulating cuproptosis in AKI remains unexplored. This study investigates the effects of reduced GSH on cuproptosis in a sepsis-induced AKI mouse model.Methods A sepsis mouse model was established via cecal ligation and puncture (CLP). Reduced GSH was administered to CLP-induced mice. Survival rates, bacterial load, inflammatory cytokine levels, oxidative stress markers, kidney function, copper (Cu) levels, and the expression of SLC31A1 were evaluated.Results Reduced GSH treatment significantly improved survival rates and reduced bacterial loads in CLP mice. Additionally, reduced GSH attenuated inflammation and oxidative stress in the septic mice. It restored kidney function, decreased Cu levels in both urine and kidney tissues, and downregulated the expression of SLC31A1.Conclusion Reduced GSH ameliorates sepsis-induced AKI by suppressing cuproptosis, offering potential therapeutic implications for the management of AKI in septic conditions.